Ibn Taymiyya’s theory of exegesis: rejecting the Ḥaqīqa-Majāz dichotomy - Kundra, Isa (AUC Knowledge Fountain, 2019)
This thesis examines a crucial pillar of Ibn Taymiyya’s exegetical methodology: his fierce critique and rejection of the ḥaqīqa-majāz dichotomy in Quranic exegesis. In doing so, I particularly investigate the epistemological and theological motivations for his rejection of the dichotomy. In the first part of the thesis, I discuss some of the difficulties in the perennial task of textual analysis, especially when attempting to decipher divine intent in the Quran (Chapter 2). Then, I set the stage by introducing the ḥaqīqa-majāz dichotomy, the linguistic feat that it attempts to explain in kalām al-‘arab, and the way it serves as the intellectual apparatus for the application of ta’wīl to Quranic exegesis (Chapter 3). Subsequently, I look at popular approaches to ta’wīl, especially amongst Ibn Taymiyya’s interlocutors, including the rational theologians and the Muslim philosophers, in order to depict Ibn Taymiyya’s intellectual milieu (Chapter 4). In the second half of the thesis, I examine Ibn Taymiyya’s critique of the dichotomy and ta’wīl in detail, which includes a metaphysical and rational critique, and I also introduce his alternative interpretive model—a contextual theory of interpretation (Chapter 5). Only at this point does it become clear that Ibn Taymiyya’s project is motivated by theological concerns, in particular those pertaining to the anthropomorphic verses (Chapter 6). I then discuss Ibn Taymiyya’s method of approaching the anthropomorphic verses and provide a general explanation of his exegetical methodology, which maintains a serious commitment to the methodology of the salaf (Chapter 7). I conclude with philosophical reflections over the tashbīh-tanzīh issue by revisiting the question of the limits of language in conveying divine reality (Chapter 8).